An electrochemical oxidative multicomponent cascade annulation of ketones and amines used to produce imidazoles. Issue 11 (9th April 2020) - Zeng, Liang; Li, Jing; Gao, Jun; Huang, Xunhai; Wang, Wei; Zheng, Xiaohui; Gu, Lijun; Li, Ganpeng; Zhang, Shengyong; He, Yonghui
Abstract : An electrochemical dehydrogenative [2 + 2 + 1] annulation used for the synthesis of imidazoles has been developed under undivided electrolytic conditions. Abstract : An electrochemical dehydrogenative [2 + 2 + 1] annulation used for the synthesis of imidazoles has been developed under undivided electrolytic conditions. In an undivided cell, aryl ketones and amines can smoothly participate in this transformation to furnish a variety of substituted imidazoles. The reaction avoids the use of both transition-metal catalysts and peroxide reagents, which makes it more sustainable and renewable.